Minat Remaja Di Jemaat Musafir Paisubololi Untuk Melanjutkan Pendidikan Di Program Studi Teologi - Molindako, Edward; Mosooli, Ermin Alperiana; Lembolangi, Lefran (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This research examines the interest of adolescents from the Musafir Paisubololi congregation in the Theology Study Program, focusing on six indicators: "enjoyment of the Theology Study Program", "motivation to enter the Theology Program", "encouragement from others", "interest in the Theology Program", "willingness to learn about religion and engage in service", and "belief in the excellence of the Theology Program". The subjects of the study were 38 adolescents aged 15-22 years. The research method was quantitative, utilizing a survey approach with data collection conducted through a Likert scale questionnaire. The findings indicate an average response of "agree" across all six indicators, with "enjoyment of the Theology Study Program" and "willingness to learn about religion and engage in service" scoring the highest. While support from parents and church leaders was significant, it needs improvement. Based on these findings, it can be concluded that there is significant potential for developing the interest of adolescents in the field of theology through increased socialization and information about career prospects and the advantages of the Theology Study Program to enhance their interest.